Conservative Management of Patent Ductus Arteriosus in Preterm Infants—A Systematic Review and Meta-Analyses Assessing Differences in Outcome Measures Between Randomized Controlled Trials and Cohort Studies - Hundscheid, Tim; Jansen, Esther J. S.; Onland, Wes; Kooi, Elisabeth M. W.; Andriessen, Peter; de Boode, Willem P. (Frontiers in Pediatrics, 2021)
Objective: to evaluate outcome after conservative management (no pharmacological/surgical intervention other than fluid restriction, diuretics or ventilator adjustments) compared to active (pharmacological and/or surgical) treatment for patent ductus arteriosus (PDA) in preterm infants and analyse differences in outcome between randomised controlled trials (RCTs) and cohort studies. Study design: systematic literature review using PubMed, EMBASE and Cochrane library. RCTs and cohort studies comparing conservative management with active treatment were included. Meta-analysis was used to compare conservative management with any active (pharmacological and/or surgical), any pharmacological (non-prophylactic and prophylactic), and/or surgical treatment for mortality as primary and major neonatal morbidity as secondary outcome measure. Fixed-effect analysis was used, unless heterogeneity (I2) was >50%. Outcome is presented as relative risk (RR) with 95%-confidence interval. Results: twelve cohort studies and four RCTs were included, encompassing 41,804 and 720 patients, respectively. In cohort studies conservative management for PDA was associated with a significantly higher risk for mortality (RR 1.34 [1.12-1.62]) but a significantly lower risk for bronchopulmonary dysplasia (RR 0.55 [0.46-0.65]), necrotizing enterocolitis (RR 0.85 [0.77-0.93]), intraventricular haemorrhage (RR 0.88 [0.83-0.95]) and retinopathy of prematurity (RR 0.47 [0.28-0.79]) compared to any active PDA treatment. Meta-analysis of the RCTs revealed no significant differences in outcome between conservative management and active treatment. Conclusion: while cohort studies suggest that conservative management is associated with a higher risk for mortality but a lower risk for morbidity, no differences were observed in RCTs. Our meta-analysis highlights the lack of high quality evidence for conservative management for PDA in preterm infants.